Geography of Olympic Combat Sports. Part three: dominance - Baginska, J.; Piepiora, Z. N.; Piepiora, P. A. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2025)
Background. This article continues a new interdisciplinary line of research into the geography of Olympic combat sports.